The Conduct of War 1789-1961; a study of the impact of the French, Industrial and Russian Revolutions on war and its conduct. - Hamman, D.S. (Scientia Militaria - South African Journal of Military Studies, 2011)
1 War has been part of Europe for many years and has been the constant occupation of her turbulent peoples. Nevertheless, not one of them since the Thirty Years' War has been so catastrophic as the wars of the present century. Yet the reason is not to be sought in war itself, but in its conduct as related to the great revolutions since 1789: the decay of aristocracy and the advent of democracy, the developments of industry and capitalism, the emergence of the masses and of socialism, the progress of science and the advances in technology, the growth of populations and the popular press, the decay of religion and ever-advancing materialism.2. All these vast changes have recast civilization, and had their impacts on warfare been diagnosed, and the conduct of war shaped accordingly, there is no reason why the world of today should be in its present mess.